The case for increasing the posting rate in delay/Doppler altimeters. Issue 2 (15th July 2021) - Egido, Alejandro; Dinardo, Salvatore; Ray, Christopher
Abstract: In this paper we analyze the effect of increasing the posting rate of delay/Doppler altimeters on the retrieval of open ocean geophysical parameters. The conventional posting rate for synthetic aperture radar altimeters data is 20 Hz, which on-ground corresponds to the typical delay/Doppler along-track resolution of about 320 m. However, the speckle autocorrelation properties of delay/Doppler waveforms over the open ocean show a decorrelation distance much shorter than the typical along-track resolution, suggesting that further information can be extracted if more frequent observations of the surface were obtained. By processing one cycle of Sentinel-3A data at different posting rates we have verified that a relative improvement of more than 20% in the measurement noise of both sea surface height and significant wave height can be achieved, just by increasing the posting rate from 20 to 40 Hz, and an even further improvement is obtained at 80 Hz. We believe this result has significant implications for the current CryoSat-2 and Sentinel-3 missions and the upcoming Sentinel-6/Jason-CS mission.